2016
DOI: 10.2169/internalmedicine.55.5876
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of the Forced Oscillation Technique

Abstract: The forced oscillation technique (FOT) is a noninvasive method with which to measure respiratory system resistance and reactance during tidal breathing. Recently, its clinical application has spread worldwide with the expansion of commercially available broadband frequency FOT devices, including MostGraph and Impulse Oscillometry. An increasing number of reports have supported the usefulness of the FOT in the management of asthma and chronic obstructive pulmonary disease (COPD). However, the FOT is not a surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 46 publications
8
88
1
Order By: Relevance
“…However, correlation coefficients in these previous reports showed only fair–moderate agreement. Shirai and Kurosawa reported that FOT is not a surrogate test for spirometry, because the tests are not identical 16. Consistently with previous reports, the present study demonstrated that most FOT indices are significantly correlated with spirometric indices, but the correlation is only fair–moderate.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, correlation coefficients in these previous reports showed only fair–moderate agreement. Shirai and Kurosawa reported that FOT is not a surrogate test for spirometry, because the tests are not identical 16. Consistently with previous reports, the present study demonstrated that most FOT indices are significantly correlated with spirometric indices, but the correlation is only fair–moderate.…”
Section: Discussionsupporting
confidence: 89%
“…Respiratory impedance was measured using a commercially available multifrequency FOT device (MostGraph-01; Chest MI, Tokyo, Japan) as previously reported1214 and following standard recommendations 16,17. Briefly, oscillatory signals generated by a loudspeaker at 0.25-second intervals were applied to the respiratory system through a mouthpiece during tidal breathing at rest.…”
Section: Methodsmentioning
confidence: 99%
“…R5‐R20, often termed frequency dependence of resistance, correlated significantly to R tot , S acin and LCI at most time‐points before and after the inhaled allergen challenge and to S cond 23 hours post‐challenge. R5‐R20 has in some publications been interpreted as an index of peripheral airway resistance, while others have stated that it should be viewed as a heterogeneity of ventilation . Based on our findings, we hypothesize that both peripheral airway resistance and ventilation heterogeneity are associated with an increased R5‐R20.…”
Section: Discussionsupporting
confidence: 66%
“…Wheezing during resting expiration is considered to be a more severe symptom than that during forced expiration [16]; thus, if the patient is found to have wheezing in a clinical interview, which is assumed that asthma is inadequately controlled, the treatment strategy would be re-evaluated. The respiratory reactance indicators Fres and AX are considered to primarily reflect the elastic properties of the respiratory system [17], and are associated with small-airway dysfunction in asthma [18]; however, the clinical significance Open Journal of Respiratory Diseases of Fres and AX remains unclear. Both Fres and AX were high, not only in the groups with inadequately controlled asthma, but also in the high-score groups for limitation of normal daily activities and shortness of breath, which are exercise-induced symptoms.…”
Section: Discussionmentioning
confidence: 99%